Mali : Request for a Three-Year Arrangement under The Extended Credit Facility-Staff Report; Informational Annex; Staff Statement; Press Release on the Executive Board Consideration; and Statement by the Executive Director for Mali. (IMF Staff Country Reports; Country Report, 2013)
This paper discusses Mali's Request for a Three-Year Arrangement Under the Extended Credit Facility (ECF). The economy is recovering and inflationary pressures have abated. After a 0.4 percent GDP decline in 2012, Mali's economy is on the mend. The improvement in the security situation and the resumption of donor assistance has helped revive business confidence. Activity is picking up in the service sectors hardest hit by the crisis (commerce, hotels, and restaurants). The banking sector is showing signs of strain. Resumption of donor support brightens the economic outlook; however, the generally positive outlook is subject to several risks.